2019
DOI: 10.3389/fneur.2019.00382
|View full text |Cite|
|
Sign up to set email alerts
|

The Blood-Brain Barrier Breakdown During Acute Phase of the Pilocarpine Model of Epilepsy Is Dynamic and Time-Dependent

Abstract: The maintenance of blood-brain barrier (BBB) integrity is essential for providing a suitable environment for nervous tissue function. BBB disruption is involved in many central nervous system diseases, including epilepsy. Evidence demonstrates that BBB breakdown may induce epileptic seizures, and conversely, seizure-induced BBB disruption may cause further epileptic episodes. This study was conducted based on the premise that the impairment of brain tissue during the triggering event may determine the organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 55 publications
4
27
0
Order By: Relevance
“…We hypothesize that at least 30 min to a couple of hours are required to induce the BBB leakage. 25 Shorter durations as those used in take-off and landing experiments were not sufficient to induce BBB leakage even at high gravity intensity. This mechanism could be related to: (1) impairments of the vestibular and/or sympathetic regulations of cerebral blood flow and cerebrospinal fluid that can alter the tight junctions and their regulations in endothelial cells to reduce the resistance of the BBB via the modification of shear stress induced by adaptation to 2 × g, as proposed on endothelial cell lines 31,32 , or (2) a modification of the ratio between local blood pressure and cerebrospinal fluid, inducing pressure-evoked endothelial cell responses.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We hypothesize that at least 30 min to a couple of hours are required to induce the BBB leakage. 25 Shorter durations as those used in take-off and landing experiments were not sufficient to induce BBB leakage even at high gravity intensity. This mechanism could be related to: (1) impairments of the vestibular and/or sympathetic regulations of cerebral blood flow and cerebrospinal fluid that can alter the tight junctions and their regulations in endothelial cells to reduce the resistance of the BBB via the modification of shear stress induced by adaptation to 2 × g, as proposed on endothelial cell lines 31,32 , or (2) a modification of the ratio between local blood pressure and cerebrospinal fluid, inducing pressure-evoked endothelial cell responses.…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, if we consider that this leakage is also possible just after 24 h of exposure to 2 × g, we confirm that an alteration of the BBB could be a rapid, localized and reversible process, as recently reported during epileptic seizure. 25 Finally, the BBB leakage induced by gravity changes could be temporary and this question should be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…We and other investigators reported that seizures can cause temporary BBB leakage. 11,12) This change could affect estradiol transport between the peripheral blood and the central nervous system (CNS), although it is difficult to recruit healthy voluntary infants for the collection of CSFs.…”
Section: Resultsmentioning
confidence: 99%
“…32 Several hypotheses exist that associate cerebrovascular permeability with epileptogenesis, including asymmetric ion and molecule distribution and other changes to neuronal homeostasis (see Dadas et al 33 for review). [34][35][36] In one model, microvascular dysfunction was evaluated on T1-weighted contrast enhanced and T2-weighted images within 2 days of status epilepticus (SE), an epileptogenic injury that precedes epilepsy development in all animals, and BBB dysfunction in the piriform network was found to be a sensitive and specific predictor of epilepsy (area under the curve [AUC] = 0.96, P < .0001). [34][35][36] In one model, microvascular dysfunction was evaluated on T1-weighted contrast enhanced and T2-weighted images within 2 days of status epilepticus (SE), an epileptogenic injury that precedes epilepsy development in all animals, and BBB dysfunction in the piriform network was found to be a sensitive and specific predictor of epilepsy (area under the curve [AUC] = 0.96, P < .0001).…”
Section: Bbb Disruption and Hippocampal Atrophy After Induced Tbimentioning
confidence: 99%
“…BBB pathology and its relationship to emergent epilepsy have been demonstrated in experimental models. [34][35][36] In one model, microvascular dysfunction was evaluated on T1-weighted contrast enhanced and T2-weighted images within 2 days of status epilepticus (SE), an epileptogenic injury that precedes epilepsy development in all animals, and BBB dysfunction in the piriform network was found to be a sensitive and specific predictor of epilepsy (area under the curve [AUC] = 0.96, P < .0001). 20 In addition, structural alterations have been found in hippocampal subfields in a study of lateral fluid percussion injury (LFP): Ipsilateral hippocampal deformation 1 week postinjury acquired from MRI-based large-deformation high-dimensional mapping showed increased lateral regions in rats that developed PTE compared with reduced medial and ventral regions in nonepileptic rats.…”
Section: Bbb Disruption and Hippocampal Atrophy After Induced Tbimentioning
confidence: 99%